2007
DOI: 10.1007/s10350-006-0753-5
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict the Development of Ischemic Colitis Among Patients with Lower Abdominal Pain?

Abstract: Old age, hemodialysis, hypertension, diabetes mellitus, hypoalbuminemia, and constipation-inducing medications are clinically important risk factors for ischemic colitis in patients experiencing lower abdominal discomfort with or without bloody stool. By considering these factors, we were able to predict with high accuracy the development of ischemic colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In routine clinical experience, conditions predisposing to ischemic colitis-be they of a vascular, cardiogenic, iatrogenic or coagulatory nature--are common among elderly people [13]. The findings of population studies suggesting hypertension, diabetes mellitus and many drugs currently prescribed for the elderly as factors able to predict cases of ischemic colitis have little discriminatory power for the geriatrician [14,15]. Our study was conducted with a control group of geriatric-age patients to establish the risk factors for IC that best characterize the elderly population.…”
Section: Discussionmentioning
confidence: 98%
“…In routine clinical experience, conditions predisposing to ischemic colitis-be they of a vascular, cardiogenic, iatrogenic or coagulatory nature--are common among elderly people [13]. The findings of population studies suggesting hypertension, diabetes mellitus and many drugs currently prescribed for the elderly as factors able to predict cases of ischemic colitis have little discriminatory power for the geriatrician [14,15]. Our study was conducted with a control group of geriatric-age patients to establish the risk factors for IC that best characterize the elderly population.…”
Section: Discussionmentioning
confidence: 98%
“…The investigators found that age greater than 60 years, hemodialysis, diabetes mellitus, hypertension, hypoalbuminemia, and use of constipation-inducing medications were associated with having ischemic colitis. 7 A recent retrospective, case-control study sought to examine the role of cardiovascular disease, cardiovascular risk factors, and treatment on the development of ischemic colitis. A total of 161 cases of ischemic colitis presenting from 1998 to 2003 were matched with 322 controls.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In a minor percentage of cases, IC can be due to occlusive causes (37.5% in our series) as IMA thrombosis or embolism [27]. The IMA occlusion is detected at enhanced CT as luminal defect [28].…”
Section: Discussionmentioning
confidence: 99%